Analisis Perbandingan Pendidikan Karakter di Jepang dan Indonesia - Rozy Wulandari; Mislaini Mislaini; Nada Ranjani (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Character education is an important aspect in forming a generation with integrity and morals. This research aims to analyze the comparison of character education in Japan and Indonesia, including understanding, character education systems, problems and implementation. A qualitative approach using literature study methods was used to explore policies, curricula and character education practices in both countries. The research results show that Japan emphasizes the values ​​of togetherness, discipline and responsibility through integration in daily life at school, while Indonesia focuses more on strengthening religious values, nationalism and morality through special subjects. Differences in cultural context and education systems are the main factors influencing each country's approach. This research is expected to contribute to the development of a more effective character education model in Indonesia by adopting best practices from Japan.